Kemampuan Menyelesaikan Soal HOTS Ditinjau dari Hasil Belajar Siswa SDI Ibnu Syam - Alif Septriansyah; M Imamuddin; Isnaniah Isnaniah (Institut Agama Islam Hidayatullah Batam, 2024)
The purpose of this study is to reveal the ability of Islamic elementary school students in solving HOTS-based math problems based on students' mathematical abilities. This research is a descriptive qualitative research. The research was conducted on grade VI students of SDI Ibnu Syam. Students' mathematical ability is measured by giving tests in the form of questions related to building space material, and students' ability to solve HOTS questions. The results of this study are that students with high, medium and low mathematical abilities have difficulty and have not been able to solve HOTS problems. This is due to the lack of habituation in working on HOTS level problems which makes students not accustomed to thinking at a high level in solving HOTS problems.